2019
DOI: 10.1111/josh.12812
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Adolescent Girls' Perceptions and Experiences of School‐Based Physical Activity to Inform the Girls' Peer Activity Intervention Study

Abstract: BACKGROUND Adolescent girls are likely to be less active than adolescent boys. A range of factors including multiple psychosocial aspects are thought to influence their engagement in physical activity (PA). This study aimed to explore adolescent girls' perceptions and experiences of school‐based PA to inform a subsequent intervention, the Girls Peer Activity (G‐PACT) project. METHODS The Youth Activity Profile was used to assess adolescent girls' current PA levels. Open‐ended questions were used to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 44 publications
(93 reference statements)
1
21
0
1
Order By: Relevance
“…PA was also identified based on the PE teacher’s subjective classification [ 29 ] or by recurring to accelerometry [ 30 ]. Overall, the majority of studies collecting the adolescent’s PA levels, have involved and considered in the analysis the perspectives of (i) active adolescents [ 31 , 32 , 33 ]; (ii) adolescents who have been active for the last 8 years [ 34 ]; (iii) adolescents with different levels of PA [ 27 , 29 , 30 , 35 , 36 , 37 ]; and (iv) inactive or low active adolescents [ 38 , 39 , 40 ]. Two studies involved adolescents from diverse PA levels but did not stratify the results based on the identified PA levels [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PA was also identified based on the PE teacher’s subjective classification [ 29 ] or by recurring to accelerometry [ 30 ]. Overall, the majority of studies collecting the adolescent’s PA levels, have involved and considered in the analysis the perspectives of (i) active adolescents [ 31 , 32 , 33 ]; (ii) adolescents who have been active for the last 8 years [ 34 ]; (iii) adolescents with different levels of PA [ 27 , 29 , 30 , 35 , 36 , 37 ]; and (iv) inactive or low active adolescents [ 38 , 39 , 40 ]. Two studies involved adolescents from diverse PA levels but did not stratify the results based on the identified PA levels [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…For those which did, SES was often reported at a general level and not used in the analysis. Some studies, however, involved only adolescents with a low SES [ 37 , 43 ] or explicitly contrasted the voices of adolescents with a low and a high SES [ 27 , 36 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This work suggested activities that required no change of uniform and could be performed with friends, during the school day, were likely to be accepted and encourage participation [37]. It is recognised that enjoyment of physical activity is positively correlated with physical activity participation levels for adolescents [38] and research has shown that lowactive girls enjoy non-competitive physical activity within the school setting and enjoy physical activity when participating with friends [39]. Research has shown that friends engage in similar levels of physical activity and physical activity interventions within the peer group may be effective as friendship can influences physical activity behaviour [40].…”
Section: Introductionmentioning
confidence: 92%